Analisis Beberapa Faktor Terhadap Keputusan Pembelian Mobil Toyota Kijang Innova (Studi Kasus Pada Masyarakat Surakarta) - Habib, Candra Rahmitha; , Kusdiyanti, SE., M.Si (2016)
This study aims to investigate the influence of several factors on purchase decisions toyota car. The sample in this study is the people who use the car Toyota Kijang Innova product areas surakarta totaling 49 respondents. The sampling technique in this research is purposive sampling and convenience sampling. Data analysis methods used were normality test and test multiple linear regression analysis with t-test, F, and the coefficient of determination (R2). In this study the data meet for a normal distribution. Hypothesis tests showed the product quality, price, and brand image have significant influence with t respectively 3.866, 2.023 and 0201. In the F test showed that jointly variable product quality, price, and brand image significantly influence purchasing decisions with a probability value of 0.000 (0.000 <0.05). The coefficient of determination (R2) of 42.1%